Making and Breaking Family: North Korea's Zainichi Returnees and "the Gift". Issue 3 (1st September 2016) - Bell, Markus Peter Simpson
Abstract : From 1959 to 1984, some 90, 000 Koreans migrated from Japan to North Korea as part of the "repatriation movement." Enduring severe deprivation in North Korea, in the last decade some 300 of these individuals have returned to Japan. Based on a year of ethnographic fieldwork in Japan, this paper asks how gift giving and the attendant obligation to reciprocate impacts on relations between non-profit organizations (NPOs) and the people they seek to help. I answer this question by examining the resettlement of returnees from North Korea, and their relationship to members of Japanese civil society. The organizations working with returnees primarily consist of elderly Japanese men who aid returnees out of guilt for their support in the 1960s and 1970s of the socialist left, North Korea, and the repatriation movement. Their assistance engenders a feeling of debt in the people they help. Returnees try to mitigate this debt by performing acts of "flexible filial piety" toward NPO members. But returnees' attempts to renegotiate the burden of the gift consequently endanger themselves and their families who remain in North Korea.